Correlation of Paraoxonase-1 with the Severity of Crohn’s Disease - Katarzyna Szczeklik; Tomasz Mach; Dorota Cibor; Danuta Owczarek; Jacek Sapa; Monika Papież; Jolanta Pytko-Polończyk; Wirginia Krzyściak (Molecules, 2018)
Diagnostics of Crohn’s disease (CD) requires noninvasive biomarkers facilitating early detection and differentiation of the disease. Therefore, in this study, we aimed to determine the relationship between paraoxonase-1 (PON-1), the severity of CD, oxidative stress, and inflammation in CD. The CD activity index was based on the current classification. Plasma PON-1 was measured in 47 patients with CD, and in 23 control volunteers. Using quantitative variables such as receiver operating characteristics (ROC) (area under the curve (AUC)), the diagnostic utility of PON-1 in differentiating the severity of CD was assessed. Circulating PON-1 was found to be decreased in the CD group compared to the control group (269.89 vs. 402.56 U/L, respectively), and it correlated well with the disease activity. PON-1 correlated positively with hemoglobin (Hb) (r = 0.539, p < 0.001), hematocrit (Ht) (r = 0.48, p < 0.001), total cholesterol (TC) (r = 0.343, p < 0.001), high density lipoprotein (HDL) (r = 0.536, p < 0.001), low density lipoprotein (LDL) (r = 0.54, p < 0.001), and triglyceride (TG) (r = 0.561, p < 0.001) and correlated negatively with white blood cell count (WBC) (r = −0.262, p = 0.029), platelet count (PLT) (r = −0.326, p = 0.006), C-reactive protein (CRP) (r = −0.61, p < 0.001), and malondialdehyde (MDA) (r = −0.924, p < 0.001). PON-1 as a marker for CD differentiation possessed a sensitivity and specificity of 93.62% and 91.30%, respectively. CD was found to be associated with the decrease in the levels of PON-1, which correlates well with activity of the disease and reflects the intensification of inflammation, as well as intensified lipid peroxidation. High sensitivity and specificity of PON-1 determines its selection as a good screening test for CD severity.